DAMPAK INFLASI DAN NILAI TUKAR TERHADAP PERTUMBUHAN EKONOMI - Munandar Makmur; Herman Sjahruddin; Deni Deni; Chandrasasmito Chandrasasmito; Dian Puspitasari; Nurul Atika Satri (Jurnal Bina Bangsa Ekonomika, 2023)
This study was conducted to analyze the impact of inflation and exchange rate changes on Indonesia's economic growth. This research uses a quantitative paradigm that seeks to explore the causes of high and low economic growth in Indonesia. The population in this study is all 38 provinces, sampling techniques using the Purposive sampling method with the number of samples that meet the criteria as many as 34 provinces. The analysis used in hypothesis testing is Panel Data Regression Analysis with the help of Eviews 12 software. The results showed that variable inflation had a positive and real effect on economic growth in addition to the Exchange Rate showed a negative and significant effect on economic growth